Positive Solutions for a Class of Fourth-Order Boundary Value Problems in Banach Spaces - Jingjing Cai; Guilong Liu (Abstract and Applied Analysis)
Using a specially constructed cone and the fixed point index theory, this work shows existence and nonexistence results of positive solutions for fourth-order boundary value problem with two different parameters in Banach spaces.